Nonprofit Board Balance and Perceived Performance. Issue 4 (June 2015) - Cumberland, Denise M.; Kerrick, Sharon A.; D'Mello, Jason; Petrosko, Joseph M.
Abstract : Based on prior literature, this article offers a reconciliation of the core roles of nonprofit boards and aligns these role‐sets with organizational theories. A survey instrument was developed and validated to measure each of four role‐sets (monitoring, supporting, partnering, and representing) to assess whether emphasis on specific roles affects board members' perception of performance. Our study of nonprofit boards in a midsized midwestern city found that balance across the role‐sets was associated with effective organizational performance. Furthermore, when board members describe any of the four role‐sets as deficient, they perceive the organization as less effective. The results of the study provide practitioners with a validated survey tool that provides nonprofit boards with a method to identify which roles their board emphasizes.